On the Ownership of Text. - Wilks, Yorick (Computers & the Humanities, 2004)
The paper explores the notions of text ownership and its partial inverse, plagiarism, and asks how close or different they are from a procedural point of view that might seek to establish either of these properties. The emphasis is on procedures rather than on the conventional subject division of authorship studies, plagiarism detection etc. We use, as a particular example, our research on the notion of computational detection of text rewriting, in the benign sense of a standard journalist's adaptation of the Press Association newsfeed. The conclusion is that, whatever may be the case in copyright law, procedural detection and establishment of the ownership is a complex and vexed matter. Behind the paper is an unspoken appeal to return to an earlier historical phase, one where texts were normally rewritten and rewritten again and the ownership of text by an individual was a less clear matter than in historically recent times.